Detection and Genomic Characterization of a Morganella morganii Isolate From China That Produces NDM-5 - Guo, Xiaobing; Rao, Yuting; Guo, Lihua; Xu, Hao; Lv, Tao; Yu, Xiao; Chen, Yunbo; Liu, Na; Han, Huiming; Zheng, Beiwen (Frontiers in Microbiology, 2019)
The increasing prevalence and transmission of the carbapenem resistance gene blaNDM–5 has led to a severe threat to public health. So far, blaNDM–5 has been widely detected in various species of Enterobacterales and different hosts across various cities. However, there is no report on the blaNDM–5– harboring Morganella morganii. In January 2016, the first NDM-5-producing Morganella morganii L241 was found in a stool sample of a patient diagnosed as recurrence of liver cancer in China. Identification of the species was performed using 16S rRNA gene sequencing. Carbapenemase genes were identified through both PCR and sequencing. To investigate the characteristics and complete genome sequence of the blaNDM–5-harboring clinical isolate, antimicrobial susceptibility testing, S1 nuclease pulsed field gel electrophoresis, Southern blotting, transconjugation experiment, complete genome sequencing, and comparative genomic analysis were performed. M. morganii L241 was found to be resistant to broad-spectrum cephalosporins and carbapenems. The complete genome of L241 is made up from both a 3,850,444 bp circular chromosome and a 46,161 bp self-transmissible IncX3 plasmid encoding blaNDM–5, which shared a conserved genetic context of blaNDM–5 (ΔIS3000-ΔISAba125-IS5-blaNDM–5-ble-trpF-dsbC-IS26). BLASTn analysis showed that IncX3 plasmids harboring blaNDM genes have been found in 15 species among Enterobacterales from 13 different countries around the world thus far. In addition, comparative genomic analysis showed that M. morganii L241 exhibits a close relationship to M. morganii subsp. morganii KT with 107 SNPs. Our research demonstrated that IncX3 is a key element in the worldwide dissemination of blaNDM-5 among various species. Further research will be necessary to control and prevent the spread of such plasmids.